EVALUASI KINERJA PENDIDIK DAN TENAGA KEPENDIDIKAN DAN PROSES PEMBELAJARAN PENDIDIKAN ISLAM DI INDONESIA - Faizah, Umi (Universitas Islam Sultan Agung, 2019)
Evaluation is a component of education that must be carried out systematically and planned as a measure of the success of the education and learning process. The author limits the discussion of evaluation of Islamic education in this article to 2 aspects, namely aspects of teacher performance and the learning process. The main problems that are often discussed related to aspects of teacher performance are the problems of teacher qualifications and competencies and the implementation of learning. While the problems faced in the learning process generally occur because of the low skill of mastering the latest technology also becomes a serious problem in the fast-paced information age. If the government previously determined four basic competencies that must be mastered by teachers in addition to a minimum educational qualification of S1 or D4, it is necessary to seriously study the offer of one new competency that must be possessed by teachers and education personnel, namely Technology Mastery Competence. Keywords: evaluation, teacher performance, learning process